Comment: Journeys to the Center of Emotion - Parkinson, B (SAGE Publications, 2013)
Does appraisal co-ordinate emotional responses? Are emotions usually reached via mental representations of relational meaning? This comment considers alternative causal routes in order to assess the centrality of appraisal in the explanation of emotion. Implicit and explicit meaning extraction can certainly help steer the course of emotion-related processes. However, presupposing that appraisals represent the driving force behind all aspects of emotion generation leads to inclusive formulations of appraisal or restrictive formulations of emotion. © The Author(s) 2013.